2008
DOI: 10.1002/msc.130
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes from a physiotherapist‐led intra‐articular hyaluronic acid injection clinic

Abstract: Physiotherapist-led intra-articular HA clinics are feasible. Clinical outcomes for individual patients are highly heterogeneous up to one year after injections. Patients with initially high levels of pain may be less likely to benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
(15 reference statements)
0
8
1
Order By: Relevance
“…Overall study quality was moderate, with only one study identified as high quality (30), and a lack of podiatry related evidence. Generalisability of the descriptive studies was limited in many cases by low response rates (under 40% response rate in 4 studies: 32, 36-38).…”
Section: Data Qualitymentioning
confidence: 97%
See 2 more Smart Citations
“…Overall study quality was moderate, with only one study identified as high quality (30), and a lack of podiatry related evidence. Generalisability of the descriptive studies was limited in many cases by low response rates (under 40% response rate in 4 studies: 32, 36-38).…”
Section: Data Qualitymentioning
confidence: 97%
“…Nine articles (30)(31)(32)(33)(34)(35)(36)(37)(38) provided evidence that physiotherapists are involved in: a) administering medicines to clients or b) advising about or recommending medicines. With the exception of a case series study (30), all were questionnaire surveys.…”
Section: Extent Of Involvement In Medicine Advice or Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Valid reliable and responsive (Birchall et al, 2008) (Aiken et al, 2008;Birchall et al, 2008;Daker-White et al, 1999) Lower extremity functional scale (LEFS) 20 items with overall score range 0-100 (worst to best)…”
Section: Pre-and Postassessment/ Baselinementioning
confidence: 99%
“…Post-assessment Valid and responsive (Kamper, Maher, & Mackay, 2009) (Birchall et al, 2008;Goodwin & Hendrick, 2016;Marks et al, 2016a;Resteghini, 2003) Questionnaire:…”
Section: Pre-and Postassessment/ Baselinementioning
confidence: 99%